2019
DOI: 10.1002/adsc.201900546
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid‐Catalyzed Asymmetric Ring‐Closing Alkylation of Inert N‐substituted Pyrroles with α, β‐Unsaturated Ketones

Abstract: A Chiral Brønsted acid catalyzed asymmetric intramolecular ring‐closing alkylation of inert pyrroles with α, β‐unsaturated ketones has been developed. This approach gave a wide range of 4‐phenyl‐4,5‐dihydro‐6H‐benzo[f]pyrrolo[1,2‐a]azepin‐6‐ones in high yields with good enantioselectivities under mild reaction conditions.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Continuing with enantioselective intramolecular Friedel-Crafts reactions, the group of Jiang developed a method for the facile construction of seven-membered heterocycles. 136 This reaction is a useful one because of the difficulty of installing chiral centres in seven-membered cycles through ring closure. It is suggested that substrates 5.40 (Scheme 61) are activated by the catalyst through H-bonding.…”
Section: 4 Additions To αβ-Unsaturated Carbonyl Compoundsmentioning
confidence: 99%
“…Continuing with enantioselective intramolecular Friedel-Crafts reactions, the group of Jiang developed a method for the facile construction of seven-membered heterocycles. 136 This reaction is a useful one because of the difficulty of installing chiral centres in seven-membered cycles through ring closure. It is suggested that substrates 5.40 (Scheme 61) are activated by the catalyst through H-bonding.…”
Section: 4 Additions To αβ-Unsaturated Carbonyl Compoundsmentioning
confidence: 99%
“…To overcome these issues, one-step methods based on the direct addition of α-alkoxyvinyllithiums (Figure A, i), Grignard reagents (Figure A, ii) to both activated and non-activated amides, or weaker nucleophiles (alkenylcerium and olefins) to secondary amides upon electrophilic activation (Figure A, iii) as well as a lithium diisopropylamide (LDA)-promoted Claisen–Schmidt condensation approach on salicylamides (Figure A, iv) have been developed. The formal alkenylation of amides using organometallic reagents could however be realized resorting to canonical multistep approaches proceeding via isolated ketone intermediates …”
mentioning
confidence: 99%
“…The formal alkenylation of amides using organometallic reagents could however be realized resorting to canonical multistep approaches proceeding via isolated ketone intermediates. 17 In the course of our studies on the reactivity of s-block polar organometallic reagents under bench-type aerobic conditions, 18 we reported a general chemoselective route to ketones from amides using non-activated N-acylpyrrolidines as privileged acylating agents of organolithiums. 19 The notorious overaddition reaction was effectively suppressed, owing to the stabilizing effect of the reaction medium [cyclopentyl methyl ether (CPME)] on the dimeric tetrahedral intermediates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving enantioselective Friedel-Crafts alkylation for inert N-substituted pyrroles with α,β-unsaturated ketone has remained unprecedented and considerably more challenging compared to those discussed so far. [102,103] This is presumably due to the weak reactivity between these two substrates and difficulties associated with controlling the stereoselectivity by traditional Lewis acid catalysis. Compared to unprotected pyrroles which are activated by interaction with the NÀ H group, the inert N-substituted pyrrole is more difficult to execute asymmetric alkylation reaction due to the absence of free NÀ H group to bind with the catalyst through H-bonding interaction.…”
Section: Intramolecular Friedel-crafts Alkylation Reactionmentioning
confidence: 99%